Determinan Harga Saham Bank Umum yang Terdaftar di BEI Pendekatan Analisis Fundamental - Putra, Moh. Rizqy Eka; Pasaribu, Gymnastiar Eka Aurillina; Putri, Icha Kartika; Fisabilillah, Ladi Wajuba Perdini; Dewi, Dita Dismalasari (Jurnal Ekonomika : INDEPENDEN, 2024)
This research aims to analyze the factors that influence the share prices of commercial banks listed on the Indonesia Stock Exchange (BEI) during the 2019-2023 period with a quantitative approach and using secondary data. The variables explained include Non-Performing Loans (NPL), Net Profit Margin (NPM), Return on Assets (ROA), and Inflation, with stock prices as the dependent variable. The method used is panel data regression with Eviews 10 software. The research results show that simultaneously, NPL, NPM, ROA and inflation have a significant effect on stock prices. Partially, NPL and inflation have no significant effect, while NPM and ROA have a significant positive effect on stock prices. These findings confirm that profitability and asset management efficiency play an important role in influencing stock prices, while credit risk and macroeconomic factors tend to have minimal influence. This research provides insight for investors and bank management in making investment decisions and managing bank financial performance..